2005
DOI: 10.1093/aob/mci237
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical Variation of Chloroplast DNA in Cork Oak (Quercus suber)

Abstract: The results support a Middle-Eastern or a central Mediterranean origin for cork oak with subsequent westward colonization during the Tertiary Period, and suggest that the 'ilex' chlorotype variation does not reflect entirely cytoplasmic introgression by Q. ilex but originated partly in Q. suber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 28 publications
(39 reference statements)
11
114
0
5
Order By: Relevance
“…Quercus morisii, instead, clearly exhibited both parental type variants, providing further elements to the ongoing investigations by Toumi and Lumaret (2001), Belahbib et al (2001), and Lumaret et al (2002) on the study of introgressive forms between Q. ilex and Q. suber. It must be noted that this relatively rare hybrid can be found only in presence of both parents.…”
Section: Hybrid Speciesmentioning
confidence: 63%
“…Quercus morisii, instead, clearly exhibited both parental type variants, providing further elements to the ongoing investigations by Toumi and Lumaret (2001), Belahbib et al (2001), and Lumaret et al (2002) on the study of introgressive forms between Q. ilex and Q. suber. It must be noted that this relatively rare hybrid can be found only in presence of both parents.…”
Section: Hybrid Speciesmentioning
confidence: 63%
“…This finding is supported by the discovery of widespread introgression of ilex-type cpDNA in Q. suber populations (Belahbib et al, 2001;Jiménez et al, 2004;Lumaret et al, 2005), whereas the opposite situation (that is, Q. ilex trees showing suber chlorotypes) is considerably less frequent. However, no evidence of unidirectional gene flow has been found in this study, because we detected a similar number of backcrosses to each species (Figure 2).…”
Section: Detection Of Hybrids In Oaksmentioning
confidence: 79%
“…Despite their deep phylogenetic divergence, clearly supported by internal transcribed spacer, amplified fragment length polymorphisms and isozyme variation (Manos et al, 1999;Toumi and Lumaret, 2001;Bellarosa et al, 2005;Ló pez de Heredia et al, 2007b), hybridization has been inferred on the basis of morphological and molecular markers (Elena-Rosselló et al, 1992;Toumi and Lumaret, 1998;Lumaret et al, 2002;Oliveira et al, 2003;Bellarosa et al, 2005). Furthermore, extensive surveys of chloroplast DNA diversity of both species and of other relatives (such as Q. coccifera) across the whole distribution range have demonstrated widespread cytoplasmic introgression, mainly localized along a northeast-southwest line, from French Catalonia and eastern Iberia to Morocco (reviewed in Lumaret et al, 2005). Interspecific exchanges seem to be limited to introgression of Q. ilex cpDNA and mtDNA into Q. suber, with only very few cases of Q. suber cpDNA introgressing into Q. ilex (Belahbib et al, 2001;Lumaret et al, 2002;Jiménez et al, 2004;Staudt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the preferential direction of hybridization involves pollination of holm oaks by cork oaks, and the common occurrence of ''ilex'' cpDNA haplotypes in cork oaks is indirect evidence of this (Belahbib et al, 2001;Jimé nez et al, 2004;Lumaret et al, 2005;Magri et al, 2007). In contrast, hardly any evidence of ''suber'' cpDNA in holm oaks has been recorded (Belahbib et al, 2001;Collada et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These hybrids are known to be fertile, as already demonstrated genetically (Oliveira et al, 2003) and previously suggested by cpDNA analysis (Belahbib et al, 2001). The backcross with cork oak would thus generate introgressed progenies which might not be as easily discriminated from the type species, and this possibility in cork production stands is construed as a potential threat to the quality of the product (Natividade, 1936(Natividade, , 1950Belahbib et al, 2001;Jimé nez et al, 2004;Lumaret et al, 2005). Early histological studies of the periderm layer of the trunk in both species and the hybrids confirmed that the intermediate morphology of the cork produced by the hybrids results from the intercalation of ritidome-like outgrowths, similar to those of holm oak (Natividade, 1936).…”
Section: Introductionmentioning
confidence: 99%